Informacyjna funkcja controllingu - Nowak, Edward (Information Function of Controlling, 2005)
Information function is an important function of controlling. This paper shows the role and importance of information system in controlling system. Central element of this system is an accounting system of an enterprise.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Finanse Bankowość Rachunkowość (2); 2005; nr 1059, s. 261-266